2019
DOI: 10.3934/krm.2019048
|View full text |Cite
|
Sign up to set email alerts
|

Numerical comparison of mass-conservative schemes for the Gross-Pitaevskii equation

Abstract: In this paper we present a numerical comparison of various mass-conservative discretizations for the time-dependent Gross-Pitaevskii equation. We have three main objectives. First, we want to clarify how purely mass-conservative methods perform compared to methods that are additionally energy-conservative or symplectic. Second, we shall compare the accuracy of energy-conservative and symplectic methods among each other. Third, we will investigate if a linearized energy-conserving method suffers from a loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 36 publications
(75 reference statements)
0
22
0
Order By: Relevance
“…When solving a NLS numerically it is therefore of great importance to also reproduce this conservation on the discrete level. This aspect was emphasized by various numerical studies [21,22], where it was also found that the complexity of the physical setup (or low-regularity) can stress this issue even further .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When solving a NLS numerically it is therefore of great importance to also reproduce this conservation on the discrete level. This aspect was emphasized by various numerical studies [21,22], where it was also found that the complexity of the physical setup (or low-regularity) can stress this issue even further .…”
Section: Introductionmentioning
confidence: 99%
“…when effects close to phase transitions are studied), then the performance of these methods can drop dramatically. Here we refer exemplarily to the recent numerical experiments reported in [19][20][21]. To overcome this issue, Ostermann and Schratz proposed new low-regularity time-integrators [19,20] which improve the convergence in low regularity regimes significantly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been applied to different NLS equation for example in the context of plasma physics [22]. For cubic nonlinearities (σ " 1 in (1)), they are linearly implicit hence very popular [4,15,6,18,20]. They preserve the L 2 -norm and a discrete analogue of (2).…”
Section: Introductionmentioning
confidence: 99%
“…Semi-implicit finite difference schemes lose most of the desired properties. A relaxation method based on a finite element spatial discretization was recently found to perform well in [24] for problems with low spatial regularity. Extensive numerical comparisons in the literature show the accuracy and efficiency of splitting methods for various quantum mechanical models under a number of different spatial discretizations, see for instance [8,16].…”
Section: Introduction and Overviewmentioning
confidence: 99%